Intraoperative haemodynamic profile in patients undergoing lower limb and abdominal surgery under subarachnoid block using 0.5% hyperbaric levobupivacaine: an observational study - Singh, Ajit Kumar; Gupta, Maruti; S., Padmini H. (International Journal of Research in Medical Sciences, 2017)
Background: The aim of this study was to detect if intrathecal hyperbaric Levobupivacaine provided anaesthesia with more stable hemodynamic profile than 0.5% Hyperbaric Bupivacaine for lower limb and abdominal surgery. Methods: This observational study was carried out on 60 Adult patients between 18-65 Years of age, in ASA I and II undergoing lower abdominal surgery. Subarachnoid block using 3.0 ml of 0.5% hyperbaric Levobupivacaine (15 mg) was used as anaesthesia for surgery. Vitals recorded first in operation theatre were taken as baseline and were compared with subsequent readings till closure to judge the fall in blood pressure. Frequencies of parameters falling more than 30% from baseline, amount of IV fluids, vasopressors administered and complications were recorded. The data collected was displayed as mean with a standard deviation and frequency with percentage. Statistical analysis was performed using in stat computer software. Results: On analysis of the data it was found that fall in hemodynamic parameters was significantly lower in the Levobupivacaine group. It was observed that maximum onset of motor block was after 5 minutes, VAS after 4 minutes and loss of pinprick sensation was achieved at T-4 level after 4 minutes. Haemodynamic complications, which required therapeutic interventions, were hypotension (5%), bradycardia (3%), a total of 8%, who required urgent intervention as vasopressors and inotropes. Conclusions: 0.5% Hyperbaric Levobupivacaine, has onset of action similar to other local anaesthetics used for subarachnoid block, but has better hemodynamic profile in comparison to Hyperbaric 0.5% Bupivacaine, the commonly used local anaesthetic agent used for Spinal Anaesthesia.